Application of SNI ISO 31000:2018 For Mitigating Problematic Murabahah Financing: A Case Study at BSI Lubuk Sikaping - Rahmayani Sania; Rini Elvira; Gusrianti Gusrianti; Imamuddin Imamuddin (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study aims to formulate a risk management strategy based on SNI ISO 31000:2018 to reduce the number of problematic murabahah financing. The research method used is qualitative with a field research approach. Data collection techniques are carried out through observation, structured interviews, and literature studies. The main informants in this study are the branch managers and the financing risk management department at BSI KCP Lubuk Sikaping. Data were analyzed using a SWOT approach through the IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation) matrices. The results show that BSI KCP Lubuk Sikaping is in quadrant I with an IFE (Internal Factor Evaluation) value of 3.41 and an EFE (External Factor Evaluation) of 3.02, resulting in an SO strategy score of 5.15, the highest compared to other strategies. This indicates that the combination of strengths and opportunities strongly supports an aggressive strategy. The five most relevant SO strategies formulated include: (1) Development of Sharia Financing Products for MSMEs; (2) Digitalization of Risk Management Systems to Support Regional Expansion; (3) Customer-Based Sharia Financial Literacy Program; (4) Improving HR Competence and Accountability in Risk Management; and (5) Strengthening SOPs and Risk Governance Based on SNI ISO 31000:2018. These strategies are expected to reduce the NPF ratio and improve the quality of the murabahah financing portfolio at BSI KCP Lubuk Sikaping.